APPLICATION STANDARD OPERATIONAL PROCEDURE (SOUP) SERVICE CANCELLATION HAJJ REGULAR ON OFFICE MINISTRY RELIGION REGENCY KAMPAR - Mayarni; Virna Museliza (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
This research was carried out at the Kampar Regency Ministry of Religion Office. The purpose of This research is to find out how standard operational procedures are implemented (SOP) for regular Hajj cancellation services at the Kampar Regency Ministry of Religion office, and to find out obstacles or inhibiting factors in implementing operational standards procedures (SOP) for regular Hajj cancellation services at the district ministry of religion office campar. The type of research used is qualitative research with an approach descriptive. Data obtained from the study This with interview, observation, And documentation. Based on the results study in the field and then in analysis with indicator efficiency, consistency, minimization error, and solution problem It can be concluded that it can be said to be not fully optimal. Because the first time the return of the initial BPIH deposit does not match what is stated in the cancellation SOP. Second, many congregations still cancel outside the provisions This has been established, for example, because of the long waiting period for the Hajj departure. And there is the obstacle that influences the implementation of the Hajj cancellation SOP is the lack of awareness of pilgrims in complete file condition cancellation so that file pilgrims this No, can directly be verified by the party officer